Comparative study on financing limit, margin of financing and safekeeping fee among Ar Rahnu operators / Mohd Shafiz Saharan ... [et al.] - Saharan, Mohd Shafiz; Jamaludin, Mohd Fazil; Adzahar, Khairul Azfar; Wagiran, Norwahida (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2021)
Ar Rahnu, or Islamic pawnbroking, is raising its popularity in Malaysia. It is one platform for public and micro entrepreneurs to get immediate financing to finance their personal or business necessities (Azman, Kassim & Adeyemi, 2016). Ar Rahnu in Malaysia started in the early '90s where it was initiated by the Terengganu State Government and known as Muassasah Gadaian Islam Terengganu (MGIT). Nowadays, most banks and nonembarked on thi bank financial intermediaries have s business due to increasing demands on the Syariah compliance pawnbroking system (Baharum, Maamor, and Othman, 2015). Ar Rahnu benefited the society by allowing them, namely individuals, small traders, and the poor, to have better and cheaper access to fi nancing without applying for retail financing products from the bank, which resulted in expensive charges and strict requirements imposed on them. Also, the Ar Rahnu financing is different from other retail financing products as it requires gold jewelry as collateral, and this financing facility is only available if the person owns it (Lawal, 2016). The collateral is deposited by a borrower and kept by the Ar Rahnu operator until full payment of the borrower's financing is settled. Not limited to that, Ar R ahn operator does not emphasize the income level or any credit background checking of the customer compared to the banks. Therefore, it is very convenient for an individual to get immediate financing even without any good financial background or income. Th is application is possible because Ar Rahnu has secured the financing by having collateral from the borrower before granting any financing (Skully, 2005).